For whom the geese toll: aberrant or adaptive behaviour in Ross’ Chen rossii and Lesser Snow geese Chen caerulescens caerulescens? - Slattery, Stuart M; Samelius, Gustaf; Alisauskas, Ray I; Danielson, Jeff R; Moore, Ferguson P (Wildfowl, 1998)
Breeding and non-breeding ducks commonly respond to terrestrial predators or novel moving objects by approaching or following such stimuli (Hochbaum 1955). This behaviour, called tolling’ (Hochbaum 1955), has been exploited to capture ducks for consumption or research (McCabe & Mulder 1961, Kear 1990, Owen & Black 1990, Karelse 1994). The adaptive significance of tolling in waterfowl is unknown but may be a curiosity (Hochbaum 1955) or mobbing response (Kear 1990, Owen & Black 1990). To our knowledge, there are no published reports of tolling by geese on Arctic breeding grounds (but see Abraham 1980). We report observations of tolling in Ross’s Chen rossii and Lesser Snow geese Chen caerulescens caerulescens (hereafter Snow Geese) and consider the potential adaptive basis for this behaviour.